DARI SUDUT BUKU MENUJU DESA LITERASI: POTENSI LITERASI ANAK DI DESA PERINA - Sidik, Lalu Israfi Ahmad; Gazali, Imam; Saputri, Intan Paraswari; Maezura, Siti; Santika, Putri Dewi; Febrianti, Fara; Selpiana, Ria; Rosalina, Nisa; Ain, Qurratul; Nugroho, Maryanto (Universitas Mataram, 2025)
The 2025 National Library Literacy Thematic Real Work Lecture (KKN) in Perina Village, Jonggat District, Central Lombok Regency was carried out to optimize the role of the Community Reading Park (TBM) or an existing but underutilized reading corner. This problem is approached with the Participatory Action Research (PAR) method which involves TBM managers, youth, and the community actively in strengthening the village literacy ecosystem. The program intervention includes three main pillars: (1) revitalization of TBM facilities, (2) implementation of creative literacy programs based on the National Library's guidelines, and (3) literacy innovations based on local wisdom. The results of the activity showed a significant increase in child participation, with an average attendance of 15-20 children per session. The innovation in the use of local folklore has proven to be effective in increasing children's enthusiasm and emotional connection to reading materials. This program has succeeded in strengthening TBM's role as a hub for community literacy and proving that culturally relevant community-based strategies are an effective implementation model to support the achievement of Sustainable Development Goal (SDG) 4: Quality Education at the grassroots level.